Islamic Religious Education Based on the Connectivism Paradigm as a Characteristic and Solution in Facing the Era of the Industrial Revolution 4.0 - Miswar (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2025)
This article focuses on the crucial role and urgency of Islamic religious education based on the connectivism paradigm in facing the Industrial Revolution 4.0 Era. This research uses a literature study or content analysis method. The results of this study indicate that the industrial revolution, characterized by the rapid development of digital technology and automation, requires a new approach to education, including Islamic religious education. Within the connectivism paradigm, Islamic religious education must effectively integrate information and communication technology (ICT) into the learning process. This article will discuss the characteristics and solutions of Islamic religious education based on the connectivism paradigm in facing the Industrial Revolution 4.0 Era.